2 Arthroscopic capsular shift surgery in patients with atraumatic shoulder instability: a randomised placebo-controlled trial. (25th January 2023) - Jaggi, Anju; Herbert, Rob; Alexander, Susan; Majed, Addie; Rudge, Will; Butt, David; Higgs, Debbie; Ginn, Karen
Abstract : Introduction: Atraumatic shoulder instability (ASI) occurs in the absence of significant trauma and can impair shoulder function. Arthroscopic capsular shift (ACS) is recommended in persistent symptoms. The primary objective of this trial was to determine the effect of ACS in ASI. Materials and Methods: A single-centre, two-arm, randomized, placebo-controlled clinical trial incorporating concealed intervention assignment, blinded assessment, and analysis by intention-to-treat was conducted. Patients over 18 years, with positive apprehension tests and evidence of capsulo-labral damage on arthroscopy, were eligible for inclusion. Participants were randomised to ACS or arthroscopy only. All patients received the same post-operative care. The primary outcome was the Western Ontario Shoulder Instability Index (WOSI), a change of 10.4 points was considered to be clinically significant. Secondary outcomes included global perceived change and episodes of dislocations. Patients were followed up at 6, 12 and 24 months. Results: 68 patients, average age 25.6 (SD 6.4), 53 females (77.9%) were randomised into the trial. Complete primary outcome data were available for 61 (90%), 59 (87%) and 56 (82%) at 6, 12 and 24 months respectively. Mean change on the WOSI scores at 6, 12 and 24 months were 5, 1 and 2 points respectively. Confidence intervals were narrow enough to rule out a clinically worthwhile beneficial effect of ACS at 6 months and the confidence intervals were nearly narrow enough to rule out clinically worthwhile effects at 12 and 24 months. Conclusion: The data suggest that ACS has no additional benefit in management of ASI compared to placebo.